Autorizações portuárias e a exploração de terminais privados no novo marco legal - Silva, Pedro Ivo Vieira (2014)
The following study deals with the exploitation of Private Port Terminals (TUP) and the treatment given by the new port statute (Law n. 12.815/2013). The study has three main aims. The first one brings the authorization as a legal instrument of public service concession for an exploitation in a more flexible system. The second one aims specifically the port authorization and the logic of the new port statute focusing on how the State interfere the exploration of TUPs. The third and last one regard the regulatory asymmetry between public and private port terminals from the perspective of public policy brought by the new port statute